Landasan Filosofis dan Budaya Feodalisme dalam Menjalankan Pemerintahan yang Demokratis di Indonesia - Sulistyono, Djoko (Research and Development Agency Ministry of Home Affairs, 2009)
Democracy is an ancient Greek cultural idea, where democracy is considered to be able to channel every aspiration of the people. With this assumption, it is assumed that there has been a harmony of relationships between people. In the sense that they form a mutually reinforcing bond, society protects citizens, while citizens will dedicate themselves to society and every citizen will be protected by the state. The implementation of democracy in each country still has to go through a process of adjustment according to the situation and conditions of each country which is based on the people's values of each country. Democracy is seen as the most appropriate and ideal embodiment for all modern political and social organizational systems.